A review of morphological characters for the identification of three common European species of Sarcophaga s. str. (Diptera: Sarcophagidae), with an emphasis on female terminalia - Schönberger, Daniel; Giordani, Giorgia; Vanin, Stefano; Whitmore, Daniel (Zootaxa, 2022)
The subgenus Sarcophaga Meigen, 1824 (s. str.) currently comprises over 30 species distributed in the West Palearctic Region, the identification of which is normally based on characters of the male terminalia. Females of the three closely-related species Sarcophaga (Sarcophaga) carnaria (Linnaeus, 1758), S. (S.) subvicina Rohdendorf, 1937 and S. (S.) variegata (Scopoli, 1763), which are especially widespread and abundant in NW Europe, are considered morphologically indistinguishable by most authors. However, a few authors have proposed keys to separate females of these three species based on external and internal characters of the terminalia. Following a preliminary molecular identification using DNA barcode sequences (COI, cytochrome c oxidase subunit I), we herein revise the morphological characters used to differentiate female S. carnaria, S. subvicina and S. variegata in existing identification keys as well as search for additional diagnostic characters. Our results suggest that only one previously-proposed female character, namely the length to width ratio of abdominal sternite 7, can be used to separate S. subvicina from the other two species (Mann-Whitney U test: p < 0.0001), at least in a majority of cases. Other characters, such as the degree of sclerotisation and setation of tergite 8, show a high degree of overlap that does not allow to reliably separate females of these three species. Nevertheless, we propose a combination of characters that should allow the separation of female S. carnaria from female S. variegata in most cases. An additional analysis of males of the same species showed that the distribution of pruinosity and setation on syntergosternite 7+8, a character mentioned in a previously-published key, is also not reliable for identification.